2013
DOI: 10.1007/s40265-013-0009-3
|View full text |Cite
|
Sign up to set email alerts
|

Certolizumab Pegol

Abstract: Certolizumab pegol (Cimzia(®)) is a recombinant, polyethylene glycolylated, antigen-binding fragment of a humanized monoclonal antibody that selectively targets and neutralizes tumour necrosis factor (TNF)-α. The drug is indicated for subcutaneous use every 2 or 4 weeks (q2w or q4w) for the treatment of adults with moderate to severe active rheumatoid arthritis (RA). The efficacy of subcutaneous certolizumab pegol in adults with active RA has been investigated in several well designed, placebo-controlled trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…It is a recombinant, polyethylene glycolylated, antigen-binding fragment of a humanized monoclonal antibody that selectively targets and neutralizes TNFα [5]. Infliximab and adalimumab are monoclonal antibodies directed toward TNFα, and etanercept is a TNF-receptor-fusion protein conjugated to the Fc portion of human IgG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a recombinant, polyethylene glycolylated, antigen-binding fragment of a humanized monoclonal antibody that selectively targets and neutralizes TNFα [5]. Infliximab and adalimumab are monoclonal antibodies directed toward TNFα, and etanercept is a TNF-receptor-fusion protein conjugated to the Fc portion of human IgG.…”
Section: Discussionmentioning
confidence: 99%
“…Induced sarcoidosis has been reported in association with infliximab, etanercept and adalimumab [1, 2, 4]. Certolizumab is a new TNFα antagonist which has been proven to be effective in the treatment of RA [5]. A review of the literature revealed no previous occurrence of sarcoidosis induced by this agent.…”
Section: Introductionmentioning
confidence: 99%
“…Three of the most successful are monoclonal antibodies targeting TNF α directly and blocking its binding to TNFRII: infliximab or remicade [ 2 ], adalimumab or Humira [ 3 ], and golimumab or Simponi [ 4 ]. Currently approved therapeutics also include an antibody Fab′ fragment conjugated to a polyethylene glycol (PEG) (certolizumab pegol or Cimzia) [ 5 7 ] and a fifth biologic, etanercept or Enbrel, which comprises of a fusion protein of TNFRII and the Fc region of human IgG1 [ 8 ]. Although targeting TNF α has been validated through proven therapeutic efficacy (and significant commercial value), not all patients respond with 25–40% of subjects failing to reach the desired ACR20 end point (20% improved response based on the American College of Rheumatology) during clinical trials [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infliximab (INF) is a chimeric mouse–human monoclonal immunoglobulin G (IgG) 1 antibody [ 17 ]. Adalimumab (ADA) [ 18 ], golimumab (GOL) [ 18 ] and certolizumab (CZP) [ 19 ] are humanized monoclonal anti-TNF-α antibodies. Etanercept (ETA) [ 20 ] is a dimeric fusion protein of the TNF receptor linked to the Fc portion of human IgG1.…”
Section: Introductionmentioning
confidence: 99%